Diagnostic Accuracy of Diffusion Weighted Imaging in Diagnosing Malignant Ovarian Lesions Keeping Histopathology as the Gold Standard - Rehman, Tooba; Ihsan, Hussain Rashid; Sadiq, Nosheen; Rasul, Tabassum; Tariq, Hassan (Pakistan Armed Forces Medical Journal, 2026)
Objective: To determine the accuracy of diffusion weighted imaging (DWI) and apparent diffusion coefficient (ADC) value in diagnosing malignant ovarian lesions.Study Design: Cross-sectional study.Place and Duration of Study: Department of Radiology, Combined Military Hospital, Multan Pakistan, from Jun 2024 to May 2025.Methodology: A total of 58 patients were enrolled in this study. They were first subjected to DWI, and ADC values were calculated to categorize ovarian masses as benign/malignant. Later, all patients underwent excision of the mass, followed by histopathological categorization of the mass as benign or malignant. The diagnostic accuracy, sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) of DWI in diagnosing malignant ovarian lesions were determined.Results: Mean age was 50.03±6.68 years, while mean BMI was 26.44±2.40 kg/m2. ADC values of malignant tumors showed a mean of 1.08 × 10-3 mm2/s±0.014, with a p-value